2010
DOI: 10.1007/s10597-010-9359-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Depression on Recovery from PTSD

Abstract: It has been suggested that the treatment strategy needs to be reviewed and changed if depression occurs in patients with posttraumatic stress disorder (PTSD). We analyzed data extracted from the Marmara Epidemiological Survey (MES) which had examined 683 survivors at 3 years after a devastating earthquake. Fifty three cases (40.5%) out of the 131 cases with PTSD had also been diagnosed with MDD. Comorbid PTSD and MDD group has significantly lower rates of recovery from PTSD in comparison to PTSD without MDD (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 30 publications
1
21
0
1
Order By: Relevance
“…At baseline, the nine SCL factors and three global indices were higher than the norm in these earthquake-related PTSD subjects, suggesting that earthquake-related PTSD is accompanied by poor GPS. These findings are consistent with those reported by other investigators [3,[59][60][61][62][63].…”
Section: Discussionsupporting
confidence: 94%
“…At baseline, the nine SCL factors and three global indices were higher than the norm in these earthquake-related PTSD subjects, suggesting that earthquake-related PTSD is accompanied by poor GPS. These findings are consistent with those reported by other investigators [3,[59][60][61][62][63].…”
Section: Discussionsupporting
confidence: 94%
“…However, it has been widely claimed that depression is the most common mental health problem among dialysis patients; this is not only because dialysis patients may have experienced multiple difficulties at home and work, for example, fatigue and sexual dysfunction, but also due to multiple stressors such as dietary constraints and dependency upon treatment [54]. Previous studies have reported that rates of comorbid depression among participants with PTSD were over 40% [30,34,55]. The rate of comorbid depression among participants with PTSD in this sample (23.1%) was lower than that found in other studies of disaster survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Tracy et al [28] suggested that PTSD and depression might be different predictors. Additionally, there are high comorbidity rates between PTSD and depression, and other mental disorders have been reported [29,30], and the presence of depressive disorders in patients with PTSD has been associated with greater functional impairment [31][32][33][34]. However, little is known about risk factors involved in comorbidity [32,34].…”
Section: Analytic Frameworkmentioning
confidence: 99%
“…One longitudinal study of civilians found that, following a traumatic event, higher reported levels of depression symptoms at each time point (measured at 1 week, 1 month, and 4 months) were related to a worsening of PTSD symptoms at the next time point (King, King, McArdle, Shalev, & Doron‐LaMarca, ). Follow‐up data from a large epidemiological study found that, among survivors of a large earthquake who had PTSD, individuals with comorbid MDD were less likely to recover from PTSD 3 years later (26.4% recovery rate) than those without MDD (47.4% recovery rate; Tural, Önder, & Aker, ).…”
mentioning
confidence: 99%